E-Commerce dan Pengetahuan Kewirausahaan dalam Meningkatkan Minat Berbisnis Masyarakat Ligkungan XX Tanjung Mulia - Bambang Sutejo; Irma Herliza Rizki; Tina Muhardika Handayani; Muammar Rinaldi (Penerbit Goodwood, 2024)
Purpose: The research aims to examine the impact of E-Commerce and Entrepreneurial Knowledge in increasing Business Interest among the community of Environment XX, Tanjung Mulia.Methodology: This study uses a descriptive quantitative method with numerical data. Primary data is collected via questionnaires distributed to residents of Environment XX, Tanjung Mulia, while secondary data is sourced from relevant literature and existing data.Results: The results of the multiple linear regression analysis show that improvements in E-Commerce and Entrepreneurial Knowledge will increase Entrepreneurial Interest. E-Commerce, in particular, has a positive and significant impact on Entrepreneurial Interest in the community of Environment XX, Tanjung Mulia, Medan. Similarly, Entrepreneurial Knowledge also has a positive and significant effect on Entrepreneurial Interest in the same area.Conclusions: Any improvement in E-Commerce and Entrepreneurial Knowledge will increase entrepreneurial interest. Both E-Commerce and Entrepreneurial Knowledge have a positive and significant partial impact on entrepreneurial interest in the community of Environment XX, Tanjung Mulia, Medan, and together they also have a positive and significant effect.Limitations: A limitation of this research is the lack of respondent diversity, as the sample was taken only from the XX Tanjung Mulia Medan community. Future research could explore other variables influencing Entrepreneurial Interest, such as business capital, family, and social support.Contribution: This research provides empirical evidence that E-Commerce is not only a technological tool, but also a factor that encourages the growth of interest in entrepreneurship in society.